Cloudberry (Rubus chamaemorus L.) cultivar ŽNybyŽ- an example of domestication of wild plant species to cultivation - Uosukainen, Marjatta (University of Eastern Finland, Faculty of Science and Forestry, Department of Biology, 2010)
v ok